2023
DOI: 10.3390/min13060713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensive Abrasion Breakage on Secondary Ball Mills for Magnetite

Abstract: In order to investigate the breakage behavior of the feed in industrial secondary ball mills, the breakage characteristics of fine magnetite were analyzed. Magnetite particle breakage produces a bimodal particle size distribution that is consistent with the typical breakage characteristics of abrasion. The secondary ball mill can increase the surface area by reducing the diameter of steel balls to enhance the abrasion. Industrial application results show that after the abrasion of the secondary ball mill for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This mechanism is related to the compressive strength and impact resistance of minerals [43,44]. For ceramic ball grinding, the instant kinetic energy of ball and mineral collisions has more difficultly in completing the breakage of minerals, the crushing process primarily relies on tangential stress-based abrasion, which is related to the wear resistance of the minerals [45].…”
Section: Cumulative Distribution Functionmentioning
confidence: 99%
“…This mechanism is related to the compressive strength and impact resistance of minerals [43,44]. For ceramic ball grinding, the instant kinetic energy of ball and mineral collisions has more difficultly in completing the breakage of minerals, the crushing process primarily relies on tangential stress-based abrasion, which is related to the wear resistance of the minerals [45].…”
Section: Cumulative Distribution Functionmentioning
confidence: 99%
“…Studies have demonstrated that the mechanical forces in ball mills facilitate the breakage and fracturing of ore particles, leading to enhanced mineral liberation. Moreover, the design and operational parameters of ball mills, such as the size and density of the grinding media [4], rotational speed [5], and the milling environment [6], significantly impact the milling performance and the energy efficiency of the process. This underscores the importance of optimizing ball milling conditions to achieve the desired mineral processing outcomes.…”
Section: Introductionmentioning
confidence: 99%